Otoritas Pemahaman Hadis Sebagai Sumber Hukum Islam: Kritik Ibn al-Labbād al-Mālikī Kepada asy-Syāfi’ī - Akmaluddin, Muhammad (Al-Mazaahib: Jurnal Perbandingan Hukum, 2021)
Understanding the hadith with different methods may have either the same result or different results, especially between ra’yu and hadith experts. The struggle for authority on understanding hadith makes this study more interesting because it involves understanding hadith itself, differences in schools of thought and which method is more authoritative in practicing a hadith. This paper discusses how Ibn al-Labbād criticized the hadith authority of as-Shafi’ī and the struggle for hadith authority and meaning. This paper uses a qualitative approach with literature review, and content analysis. The object of research in this paper is the work of Ibn al-Labbād (d. 333/944) along with his work in ar-Radd ‘alā as-Shāfi’ī. There are four categories of criticism by Ibn al-Labbād, they are: criticism of definitions, the causes of the appearance of hadith (asbāb al-wurūd), hadiths that are not fit with the verses of the Qur’an and laws that are not found in the hadith. Ibn al-Labbād’s critique of the interpretation of as-Shafi’ī is a proof that hadith text is not limited only to the understanding of the Shafi’ī school. Likewise, what was done by as-Shafi’ī also a proof so that the understanding of hadith is not only dominated and controlled by Malik.